DEVELOPMENT OF THE LABOR MARKET IN THE TRANSFORMATION ECONOMY BASED ON THE TOOL OF ARTIFICIAL INTELLIGENCE - Abdurakhmanov Kalanadar Khodjaevich; Shakarov Zafar Gafforovich (Labor economics and human capital, 2023)
This article focuses on the importance of artificial intelligence in the labor market and its impact. The author describes the ability of artificial intelligence to affect several sectors and professions in the economy, the improvement and expansion of tasks due to automation of jobs, and the positive or negative impact of artificial intelligence on wages and labor productivity.